HSD3B1 Is a Specific Trophoblast-Associated Marker Not Expressed in a Wide Spectrum of Tumors. Issue 2 (1st February 2013) - Chou, Yuh-Yu; Jeng, Yung-Ming; Mao, Tsui-Lien
Abstract : Objective: Hydroxyl-δ-5-steroid dehydrogenase (HSD3B1) is an enzyme that catalyzes the oxidative conversion of δ-5-3 β-hydroxyl steroids to the δ-4-3-keto configuration and is involved in steroid hormone synthesis. It has been shown to be expressed in normal trophoblastic tissue and benign and neoplastic trophoblastic lesions. HSD3B1 has not been detected in a large number of lung, breast, and uterine carcinomas; however, its expression has not been studied in a wide variety of other nontrophoblastic neoplasms. To test if HSD3B1 is highly specific for normal trophoblasts and trophoblast-associated lesions, we examined the expression of HSD3B1 in a wide spectrum of tumors. Methods: Tissue microarrays containing 473 carcinomas from the lung, breast, ovary, uterus, liver, pancreas, stomach, and colon; 32 ovarian granulose cell tumors; and 12 adrenocortical adenomas were studied by immunohistochemistry using a commercially available monoclonal antibody, HSD3B1. One tissue microarray containing normal tissues was also included. Positive staining of intermediate trophoblasts and syncytiotrophoblasts in normal placental tissue served as a positive control. Results: Normal tissues and tumors from the various sites were all negative for HSD3B1 except for 2 adrenocortical adenomas with weak focal immunoreactivity. Conclusions: Our study further confirmed that HSD3B1 is a highly specific trophoblast-associated marker that can be used in the distinction of trophoblastic tumorlike lesions and tumors from nontrophoblastic lesions and tumors.